El control interno y su incidencia en el cumplimiento presupuestario de la corporación Cofispi, cantón Pichincha. año 2012. - Marcillo Vélez, Legni Patricia (2014)
The internal control is a tool that allows improving the activities of the entities; the same one that has as main tools the procedures of internal control in the countable and financial area that you/they allow to assure the financial resources of the company. The application of the questionnaires to evaluate the internal control responds to the necessity of generating useful and efficient information that allows reaching the objectives with quality and efficiency for the execution of the managerial function after being analyzed in an integral way…….